Design of frequency response masking filters using window techniques - Leow, Siok Hua. (2009)
In this report, a filter is built based on frequency response masking (FRM) method and Window method. Each method has its own attractive features. For frequency response masking method, it is known to be a very efficient for the synthesis of a sharp linear phase digital filter. For the window method, it is used to reduce the Gibbs phenomenon and involves minimal amount of computation. Thorough simulations for different bandwidth and window functions demonstrate the feasibility in using frequency response masking method with windowing to achieve sharp filters with acceptable ripples.